(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Manyastambha is a type of Vataja Nanatmaja Vyadhi described under the heading of Vatavyadhi. It is characterized by symptoms like Ruk (pain) and Sthamba (stiffness) in the Manyapradesha (cervical region) of Urdwajatru Pradesha. Similar to this, there is a condition known as Cervical Spondylosis in western science based on symptomatology which is mainly due to the chronic degenerative condition of the cervical spine that affects the vertebral bodies and intervertebral discs of the neck as well as the contents of the spinal canal. The prevalence of cervical spondylosis is around 40% of the world population and may manifest in those as young as 30 years and most commonly in those aged between 40-60 years. Methodology: In the present study, a total of 30 patients were diagnosed with Manyastambha (Cervical Spondylosis). They were randomly assigned to a single group and have been treated by Rooksha Sweda (Valuka) and Bhringaraja Taila Nasya for 7 days with a follow-up of 14 days. Observations: It was observed in the present study that all subjective and objective parameters in all the 30 patients have shown significance with a p-value <0.01. Conclusion: Valuka Sweda and Nasya Karma are highly significant at P<0.001. Rooksha Sweda and Nasya Karma are the safest, simplest and most effective Panchakarma therapies in the management of Manyastambha (Cervical Spondylosis).